2018
DOI: 10.1111/codi.13966
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic local recurrence from colorectal cancer: surgical challenge with changing preconditions

Abstract: The proportion of lateral pelvic recurrences has increased over time. In comparison with non-lateral LRs, lateral LRs are more difficult to resect radically and are associated with worse overall and disease-free survival. However, with radical surgery many patients with pelvic locally recurrent colorectal cancer may be offered curative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…In recent years, there has been a trend towards centralization of the management of patients with LRRC, which will probably lead to an increase in both the overall resection rate and the proportion of R0 resections. In the present study, an R0 resection was achieved in only 45·0 per cent of patients who underwent tumour resection, compared with R0 resection rates of up to 77 per cent in specialized centres. Although selection bias cannot be excluded when comparing different reports, it is highly likely that increasing surgical skills and greater experience from higher patient volumes improve R0 resection rates and oncological outcomes.…”
Section: Discussionmentioning
confidence: 53%
“…In recent years, there has been a trend towards centralization of the management of patients with LRRC, which will probably lead to an increase in both the overall resection rate and the proportion of R0 resections. In the present study, an R0 resection was achieved in only 45·0 per cent of patients who underwent tumour resection, compared with R0 resection rates of up to 77 per cent in specialized centres. Although selection bias cannot be excluded when comparing different reports, it is highly likely that increasing surgical skills and greater experience from higher patient volumes improve R0 resection rates and oncological outcomes.…”
Section: Discussionmentioning
confidence: 53%
“…Meanwhile, R0 resection was still the only independent favorable factor for PFS among the variables related to LRRC, and this result is consistent with that of other recent reports. 21,22 Resection of LRRC impacts QoL by removing the symptom-producing lesion. In turn, getting longer PFS is to some degree linked to longer symptom-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…With the implementation of high-quality TME, there has been a gradual shift from central recurrence (in the anastomosis site and perineum) to non-central recurrence; an increased proportion of recurrences have been found to be occurring in the presacral area and the lateral pelvic wall (16)(17)(18). The presacral plane is the most easily dissected plane during surgery and is almost always included in radiotherapy.…”
Section: Timing and Risk Factors Of Local Recurrencementioning
confidence: 99%
“…The proximity to the pelvic bone and major neurovascular structures means that achieving a complete resection and negative margin is technically challenging. Thus, the lateral recurrence type has a poor prognosis (18). Austin et al (54) reported a new approach for the en-bloc resection of pelvic sidewall structures, including the internal iliac vessels, piriformis and obturator internus muscles, ischium, sacrotuberous and sacrospinous ligaments.…”
Section: Multi-organ Excisionmentioning
confidence: 99%